2017
DOI: 10.3847/1538-4357/aa6579
|View full text |Cite
|
Sign up to set email alerts
|

A History of H i Stripping in Virgo: A Phase-space View of VIVA Galaxies

Abstract: We investigate the orbital histories of Virgo galaxies at various stages of H i gas stripping. In particular, we compare the location of galaxies with different H i morphology in phase space. This method is a great tool for tracing the gas stripping histories of galaxies as they fall into the cluster. Most galaxies at the early stage of H i stripping are found in the first infall region of Virgo, while galaxies undergoing active H i stripping mostly appear to be falling in or moving out near the cluster core f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
175
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(198 citation statements)
references
References 63 publications
13
175
1
Order By: Relevance
“…In higher-mass haloes, a greater fraction of satellites are devoid of H i, with their occupancy extending to increasing radii. All of this falls in line with expectations and previous studies of ram-pressure stripping (see Gunn & Gott 1972;Yoon et al 2017).…”
Section: Context and Summary Of Resultssupporting
confidence: 92%
“…In higher-mass haloes, a greater fraction of satellites are devoid of H i, with their occupancy extending to increasing radii. All of this falls in line with expectations and previous studies of ram-pressure stripping (see Gunn & Gott 1972;Yoon et al 2017).…”
Section: Context and Summary Of Resultssupporting
confidence: 92%
“…Fig. 6 in Yoon et al 2007). At the time of observation the galaxy is crossing the 15% stripping line, and it will continue to get stripped if it reaches lower r cl .…”
mentioning
confidence: 95%
“…Gasp galaxies are highlighted with red colors. ICM, gas rich galaxies avoid the "virialised" region of phasespace (Jaffé et al 2015;Yoon et al 2017), which is populated mostly by passive galaxies quenched by the hostile cluster environment (Jaffé et al 2016;Paccagnella et al 2017). Observations of Hi in group galaxies have further suggested that the processes quenching galaxies in clusters could scale to the group regime (see results from Catinella et al 2013;Hess & Wilcots 2013;Jaffé et al 2012Jaffé et al , 2016.…”
Section: Spatially Resolved Properties Of the Gasp Galaxiesmentioning
confidence: 99%